Prospects for constitutionalism in post-communist countries - Gönenç, Levent (Law in Eastern Europe, 2002)
The main questions dealt with throughout this study can be formulated as follows: Will liberal democratic constitutionalism take root in post-communist countries? And will new constitutions in Eastern Europe and the former USSR perish or survive?